THE EFFECT OF VISA FREE TOWARD HOTEL BUSINESS SECTOR IN NORTH SULAWESI (CASE STUDY AT LION HOTEL IN MANADO) - Siahaan, Karina .; Kindangen, Paulus .; Tumbuan, Willem J.F.A (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: An increase in the number of foreign tourists coming into Indonesia, especially North Sulawesi is very high. The Government should increase the number of each facility. Foreign tourists need a wide range of facilities to enjoy every sightseeing trip in Manado. Maximizing the existing public facilities is very important. The aim of this study is to identify and analyze the Effect of Visa-free toward hotel business sector in North Sulawesi. This research used snowball analysis. The type of this research is descriptive research and used qualitative research method. Population in this research are HRD employees and marketing employees of Lion hotel. The samples of this research are 20 informants. Based on the result, this research found out that Visa-free gives effect toward Hotel business sector. The result shows that visa-free entry policy has a positive impact on the number of tourist arrivals. For hotel business, especially Lion Hotel Very need to pay attention to the things that become the criteria of customer satisfaction. In particular, in the increase in employees Â work ethic and the way employees interact with guests of the hotel in order to create a good impression for all hotel guests who visit.Â Keywords: visa free, hospitality, tourism, marketing, and snowball method.